Accuracy verification of impulse voltage measuring systems by convolution methods - Yutthagowith, P.; Pattanadech, N.; Kunakorn, A.; Phoomvuthisarn, S. (My University, 2005)
This paper presents verification of high voltage measuring systems by time convolutions between standard testing waveforms and unit step responses of the measuring systems. The waveforms under investigations are full lightning impulse voltage waveforms, tail-chopped lightning impulse voltage waveforms, front-chopped lightning impulse voltage waveforms and steep-front voltage waveforms according to IEC standards 60060-2 and 61211. This paper considers four different types of the measuring systems. The results show that this technique is applicable, and should be a useful method for impulse voltage measurements in a standard high voltage laboratory.
Keywords: Convolutions; Impulse voltage measurements